Multiple down-core scanning profiles of sediments from the East Frisian Wadden Sea (Germany) - An-Sheng Lee; Dirk Enters; Jürgen Titschack; Bernd Zolitschka (PANGAEA, 2020)
The dataset contains ten sections of sediment cores retrieved by Wadden Sea Archive (WASA) project. Four non-destructive down-core scanning techniques (magnetic susceptibility, X-ray computed tomography, X-ray fluorescence, and digital photography) were applied, and the results were analyzed to have 1-dimensional profiles. The X-ray fluorescence profiles (in elements) were transformed by principal component analysis. Meanwhile, the sedimentary facies labels are accompanied.